Economic evaluation of smallholder subsistence livestock production: Lessons from an Ethiopian goat development program - Workneh Ayalew; J. M. King; E. Burns; B. Rischkowsky (Fondazione Eni Enrico Mattei (FEEM), 2001)
Conventional productivity evaluation criteria are inadequate to evaluate subsistence livestock production, because 1) they fail to capture non-marketable benefits of the livestock, and 2) the core concept of a single limiting input is inappropriate to subsistence production, as multiple limiting inputs (livestock, labour, and land) are involved in the production process. As many of the livestock functions as possible (physical and socio-economic) should be aggregated into monetary values and related to the resources used, irrespective of whether these "products" are marketed, home-consumed or maintained for later use. A broad evaluation model involving three complementary flock-level productivity indices was applied to evaluate subsistence goat production in eastern Ethiopian highlands. The results showed that indigenous goat flocks generated significantly higher net benefits under improved than under traditional management, which challenges the prevailing notion in countries like Ethiopia that indigenous livestock do not adequately respond to improvements in the level of management. It is then concluded that the evaluation model not only allows a broad aggregation of benefits from subsistence livestock, but also provides a more realistic platform to propose sound improvement interventions.
Keywords: 330; Evaluation; indigenous animal genetic resources; Unit Net Benefits; Tierhaltung; Ziege; Subsistenzwirtschaft; Äthiopien